2016
DOI: 10.1007/s11596-016-1584-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Sox2 expression in digestive tract cancers: A meta-analysis

Abstract: The aim of the present study was to accurately evaluate the association of Sox2 expression with the survival of patients with digestive tract cancers. Relevant literatures were identified by comprehensively searching databases including the Pubmed, Embase, CBMdisc, and Wanfang (up to October 2014). A meta-analysis was performed to clarify the association between Sox2 expression and overall survival or clinicopathological parameters of patients with digestive tract cancers (esophageal, gastric, and colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…e previous meta-analysis only included eight studies with small sample sizes (n � 1113) and only analyzed the correlation between SOX2 and overall survival (OS) and a small part of the clinical features of CRC. Additionally, the result on OS was not reasonable [22]. erefore, the significance of SOX2 expression in CRC is not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…e previous meta-analysis only included eight studies with small sample sizes (n � 1113) and only analyzed the correlation between SOX2 and overall survival (OS) and a small part of the clinical features of CRC. Additionally, the result on OS was not reasonable [22]. erefore, the significance of SOX2 expression in CRC is not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…SOX2 expression is common across a wide range of human tumors, such as gastric, colorectal, lung, and ovarian cancers [16]. Its expression is closely related to worse prognosis in some types of human cancers [17, 18]. SOX2 overexpression is found in cancer metastasis [49].…”
Section: Discussionmentioning
confidence: 99%
“…CSC marker SOX2 is frequently expressed in many human cancers, such as gastric cancer, colorectal cancer, lung cancer, and ovarian carcinoma [16]. Some studies show that SOX2 expression is associated with poor prognosis in some cancers such as esophageal, colorectal, and head and neck cancers [17, 18]. However, SOX2 expression is correlated with a favorable prognosis in non-small cell lung cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis revealed that Sox2 over-expression was associated neither with the overall survival nor with the other clinicopathological factors with obvious heterogeneity[30–31]. In our study, we analyzed the data, with respect to stratification, based on tumor location and stage, we found that Sox2 had predictive value in cardiac gastric cancers or earlier stage (Stages I and II), but not in non-cardiac gastric cancers or later stage (Stages III and IV).…”
Section: Discussionmentioning
confidence: 99%